A new insight of lignin pyrolysis mechanism based on functional group evolutions of solid char. (15th March 2021) - Yang, Haiping; Dong, Zhiguo; Liu, Biao; Chen, Yingquan; Gong, Meng; Li, Shujuan; Chen, Hanping
Graphical abstract: Highlights: Lignin pyrolysis mechanism was explored with volatile and char evolution property. Alcohol O–H groups changed earlier than the carbonyl CO groups before 250 °C. The cleavage and remodeling of the aliphatic chains are synchronous. The benzene structures changed from simple substitution to complex substitution. Abstract: To elucidate the mechanism of biomass lignin pyrolysis, the functional group evolution in lignin chars derived at 200–600 °C was investigated using two-dimensional perturbation correlation infrared spectroscopy, associated with the properties of the volatile products. Results from 2D-PCIS pointed that the change in the alcohol groups C–OH occurs earlier than that in the carbonyl groups CO before 250 °C, corresponding to the reaction of keto–enol tautomerization: C–OH → CO, and the cleavage of bonds and remodeling reactions of the side chains of the benzene rings are synchronous. Besides, the formation of simple substituted benzene structures was earlier than complex substituted benzene structures. Decarbonylation, dehydrogenation and dealkylation were intensified during polycondensation of benzene rings. These findings are significant for achieving an in-depth understanding of lignin pyrolysis.